Pulmonary arterial hypertension associated with congenital heart disease: An omics study - Zhao, Maolin; Liu, Jian; Xin, Mei; Yang, Ke; Huang, Honghao; Zhang, Wenxin; Zhang, Jinbao; He, Siyi (Frontiers in Cardiovascular Medicine, 2023)
Pulmonary arterial hypertension associated with congenital heart disease (PAH-CHD) is a severely progressive condition with uncertain physiological course. Hence, it has become increasingly relevant to clarify the specific mechanisms of molecular modification, which is crucial to identify more treatment strategies. With the rapid development of high-throughput sequencing, omics technology gives access to massive experimental data and advanced techniques for systems biology, permitting comprehensive assessment of disease occurrence and progression. In recent years, significant progress has been made in the study of PAH-CHD and omics. To provide a comprehensive description and promote further in-depth investigation of PAH-CHD, this review attempts to summarize the latest developments in genomics, transcriptomics, epigenomics, proteomics, metabolomics, and multi-omics integration.